Thoroughly Exploring Secularism in an Islamic Perspective: History, Dynamics, and Interpretation of the Qur'an - Eka Cahyani M Djamil; Eka Galih Rahayu; Fahmi Fahreza (Bulletin of Islamic Research, 2024)
Secularism, a concept that emerged in the West and spread throughout the world, including Indonesia, has become a subject of debate in relation to religion, especially Islam. This research aims to explore the definition of secularism, its development in various fields, the changes that arise as a result, the interpretation of Qur'anic verses related to secularism, and scholars' perspectives on this matter. Through a qualitative method, this research utilises secondary data sources, such as journal articles and books, to provide a deeper understanding of this topic. The results show that secularism is considered as the separation of human affairs from God's affairs in all aspects of life, including education. Yusuf Qardhawi expressed his concern over the influence of secularism and atheism in the Islamic world, fuelled by colonialism and modernity. In the context of Qur'anic verses, this study found references to secularism in Surah Al-Isra' and Surah Hud. In this context, the contrast between worldly and afterlife orientations, as well as warnings against mere worldly pleasures, take centre stage. As such, this study provides a deep insight into how Islam understands and interprets secularism.